18‐2: Improvement of the Light Leakage of HUD System. Issue 1 (25th September 2020) - Kamoshida, Kenta; Tadauchi, Ryo; Shimada, Takashi; Ogura, Kenji; Murata, Mitsuhiro
Abstract : When a large backlight of high luminance is used for HUD, light leakage might occur at the corner of LCD. The detailed analysis found that photo‐elastic effect of glass and its birefringence leads to the light leakage. Also it was found that the uneven distribution of the temperature on the polarizer could be the root cause of the shrinkage. Proper introduction of wire‐grid substrate can be an effective countermeasure to improve the light leakage.